Changes in 25‐hydroxyvitamin D levels post‐vitamin D supplementation in people of Black and Asian ethnicities and its implications during COVID‐19 pandemic: A systematic review. Issue 5 (6th October 2021) - Vaughan, Megan; Trott, Mike; Sapkota, Raju; Premi, Gurmel; Roberts, Justin; Ubhi, Jaspal; Smith, Lee; Pardhan, Shahina
Abstract: Background: People of Black and Asian ethnicities have a higher infection rate and mortality as a result of COVID‐19. It has also been reported that vitamin D deficiency may play a role in this, possibly because of the multi‐gene regulatory function of the vitamin D receptor. As a result, increased dietary intake and/or supplementation to attain adequate 25‐hydroxyvitamin D (25(OH)D) levels could benefit people in these ethnicities. The present study aimed to review the literature examining the changes in 25(OH)D in different types of vitamin D supplementation from randomised controlled trials in this population. Methods: This systematic review was conducted using the PRISMA guidelines. Electronic databases were systematically searched using keywords related to vitamin D supplementation in Black and Asian ethnicities. Results: Eight studies were included in the review. All the included studies found that supplementation of vitamin D (D2 and D3 ), regardless of dosage, increased 25(OH)D levels compared to a placebo. All trials in which participants were vitamin D deficient at baseline showed increased 25(OH)D levels to a level considered adequate. Two studies that used food fortification yielded smaller 25(OH)D increases compared to similar studies that used oral supplementation (10.2 vs. 25.5 nmol L −1, respectively). Furthermore, vitamin D2 supplementation yielded significantly lower 25(OH)D increases than vitamin D3 supplementation. Conclusions: Oral vitamin D supplementation may be more efficacious in increasing 25(OH)D levels than food fortification of Black and Asian ethnicities, with vitamin D3 supplementation possibly being more efficacious than vitamin D2 . It is recommended that people with darker skin supplement their diet with vitamin D3 through oral tablet modes where possible, with recent literature suggesting a daily intake of 7000–10, 000 IU to be potentially protective from unfavourable COVID‐19 outcomes. As a result of the paucity of studies, these findings should be treated as exploratory. Highlights: Oral vitamin D supplementation could be more efficacious than food fortification in Black and Asian populations. Vitamin D3 is more efficacious than vitamin D2 . It is recommended that people with darker skin supplement their diet with vitamin D3 .